REFLECTIONS ON SOCIAL INEQUALITY IN THE MUNICIPALITY OF RONDON DO PARÁ IN THE STATE OF PARÁ - Araújo, Mylena Pereira (2024)
The present study aimed to understand social inequality in Rondon do Pará through the richest and poorest social classes. It aimed to understand social inequality in the municipality of Rondon do Pará through the richest and poorest social classes. Regarding methodology, the study is defined as qualitative and exploratory in nature, and the technique used was oral history. They were residents of the municipality in question. Data collection took place through interviews via the social network WhatsApp with a semi-structured script applied to 12 residents who fit into the research. Although both groups report having good daily meals, the definition of "good" varies between social categories. Regarding housing, interviewees in the Lower Class (CB) category tend to live in rented houses, while those in the Upper Class (CA) category own their properties, with particular emphasis on investments in real estate and automobiles.